A further specification of the effects of font emphasis on reading comprehension: Evidence from event-related potentials and neural oscillations. - Wu, Yingying; Luo, Cuixin; Wang, Zhenxing; Xie, Hanying; Huang, Yajing; Su, Yankui (Memory & Cognition, 2024)
The attention hypothesis, which assumes that font emphasis captures readers' attention, is usually used to explain the mechanism by which such emphasis operates. This study further delineates the attention hypothesis by investigating the ways in which font emphasis captures attention and its effects on the integration of emphasized information into the previous context. We computed event-related potentials and frequency band-specific electroencephalographic power changes occurring while participants read sentences containing critical words that were either emphasized (i.e., displayed in a color different from the other words in the sentence) or not (i.e., shown in the same color as the rest of the sentence) and semantically congruent with prior words or not. The results showed that the emphasized words (as compared to control words) elicited a reduced N1 and increased P2, indicating that font emphasis reduced familiarity-based visuo-orthographic processing and instead increased controlled attentional processing. We also observed greater P300 and power decreases in the alpha and beta frequency range in response to critical words in the emphasized condition, suggesting that font emphasis enhances focal attention to promote a fuller integration of information into the sentence context. Furthermore, relative to the control condition, the emphasized condition induced delta and theta power increases for the incongruent words. These results suggest that font emphasis increases the efficiency of glyph processing, which facilitates lexical access.